The Impact of Inherited Retinal Diseases in the United States of America (US) and Canada from a Cost-of-Illness Perspective - Gong J (Dove Medical Press, 2021)
Jennifer Gong,1 Simone Cheung,2 Alivia Fasso-Opie,3 Orla Galvin,4 Larissa S Moniz,5 Doug Earle,5 Todd Durham,6 Jason Menzo,6 Nan Li,7 Stephanie Duffy,7 Jill Dolgin,8 Mark S Shearman,8 Chiara Fiorani,9 Judit Banhazi,9 Avril Daly4 1Health Economics and Social Policy, Deloitte Access Economics, Melbourne, Victoria, Australia; 2Health Economics and Social Policy, Deloitte Access Economics, Sydney, New South Wales, Australia; 3Health Economics and Social Policy, Deloitte Access Economics, Canberra, Australian Capital Territory, Australia; 4Retina International, Dublin, D08 R9CN, Ireland; 5Fighting Blindness Canada, Toronto, Ontario, Canada; 6The Foundation Fighting Blindness, Raleigh, North Carolina, USA; 7The Janssen Pharmaceutical Companies of Johnson and Johnson, Raritan, New Jersey, USA; 8Applied Genetic Technologies Corporation, Cambridge, Massachusetts, USA; 9Novartis Pharma AG, Basel, SwitzerlandCorrespondence: Avril Daly Email avril.daly@retina-international.orgObjective: To estimate the annual cost of inherited retinal diseases (IRDs) in the United States of America (US) and Canada from a societal perspective – including costs to the health system, individual and family productivity costs, lost wellbeing and other societal economic costs – by setting and payer. Findings will inform the need for policy action to mitigate the impact of IRDs.Methods: The costs of IRDs were estimated using a cost-of-illness methodology, based on the prevalence of IRDs in each country. Intangible costs of reduced wellbeing were also estimated using disability-adjusted life years which were then converted to monetary values using the value of a statistical life.Results: Using base prevalence rates, total costs attributable to IRDs in the US were estimated to range between US$13,414.0 and US$31,797.4 million in 2019, comprising both economic costs (between US$4,982 and US$11,753.9 million; 37% of total costs) and wellbeing costs (between US$8,431.7 and US$20,043.6 million; 63%). Total costs attributable to IRDs in Canada were estimated to range between CAN$1637.8 and CAN$6687.5 million in 2019, comprising both economic costs (between CAN$566.6 and CAN$2,305.7 million; 34%) and wellbeing costs (between CAN$1,071.4 and CAN$4,381.9 million; 66% of total costs).Conclusion: The impact of IRDs in the US and Canada is substantial when considering both economic costs and reduced wellbeing. The wellbeing costs due to IRDs in the US and Canada are considerable, accounting for over 60% of total costs. Vision loss from IRDs often manifests in childhood, meaning some people live with vision impairment and blindness for their whole lives. Further research into current and emerging cost-effective therapies and interventions is required given the substantial economic burden faced by those living with vision loss.Keywords: genetic diagnosis, inherited retinal disease, cost-of-illness